The causal relationship between metabolic factors, drinking, smoking and intrahepatic cholangiocarcinoma: a Mendelian randomization study - Qin, Shan-shan; Pan, Guo-qiang; Meng, Qun-bo; Liu, Jin-bo; Tian, Zi-yu; Luan, Shou-jing (Frontiers in Oncology, 2023)
Background: Intrahepatic cholangiocarcinoma (iCCA) is the second most common primary liver cancer. While multiple risk factors for iCCA have been established, other risk factors including obesity, type 2 diabetes and smoking are still controversial due to the potential confounders. Here, Mendelian randomization (MR) analysis was performed to identify the causal relationship between them. Method: In this study, we obtained GWAS data which related to exposures from corresponding large genome-wide association studies. Summary-level statistical data for iCCA were obtained from UK Biobank (UKB). We performed univariable MR analysis to identify whether genetic evidence of exposures was significantly associated with iCCA risks. Multivariable MR analysis was conducted to estimate the independent effects of exposures on iCCA. Results: Univariable and multivariable MR analysis indicated that obesity, type 2 diabetes and smoking might not the risk factor for iCCA incidence. Mmultivariable MR analysis: Anthropometric traits: BMI (OR=2.057, CI= 0.508-8.324, p=0.312); Body fat percentage (OR=2.146, CI=0.154-29.896, P=0.57); Hip circumference (OR=0.994, CI=0.231-4.285, p=0.995); Waist circumference (OR=1.713, CI=0.272-10.786, p=0.568). Glycemic traits: 2h Glucose (OR=1.267, CI=0.375-4.278, p=0.703); Fasting Glucose (OR=0.592, CI=0.048-7.330, p=0.683); HbA1c (OR=0.992, CI=0.120-8.185, p=0.994); Fasting Insulin (OR=1.890, CI=0.091-39.320, p=0.681). The results were consistent in genetically predicted lipidemic traits. HDL-C (OR=0.761, CI=0.405-1.430, p=0.397); LDL-C (OR=1.226, CI=0.659-2.281, p=0.521); TG (OR=1.245, CI=0.568-2.729, p=0.585); TC (OR=0.952, CI=0.507-1.787, p=0.879); Type 2 diabetes (OR=0.685, CI=0.375-1.252, p=0.219); Smoking (OR=0.751, CI=0.292-1.934, p=0.553). Conclusion: In this MR study, we found no strong evidence to support causal associations between obesity, type 2 diabetes, smoking and iCCA risk.